Islamic Education Leadership and Character Building: Exploring the Role of Charisma in Madrasah Ibtidaiyah Management - Nurjanah, Nurjanah; Ali Anapiah; Ainiyah, Nur; Nida Nurjunaedah (UIN Sunan Gunung Djati Bandung, 2024)
This study explores the operationalisation of charismatic leadership in Islamic educational institutions, focusing on MI Nurul Amal Cikawung, Indonesia. Using a qualitative case study approach, this research investigates how charismatic leadership, characterised by transformative communication, moral integrity, and interpersonal cohesion, contributes to madrasah governance, character education, and the integration of Islamic values with modern management. Data were collected through semi-structured interviews, participatory observations, and document analyses involving the principal, teachers, and staff. The findings revealed that charismatic leadership functions as a strategic force that enhances institutional coherence, staff discipline, and pedagogical innovation. The principal's application of Islamic ethics, inclusive decision-making, and vision-driven leadership catalysed a positive organizational climate and improved collaboration among teachers. Furthermore, charisma facilitates character formation among students by embedding moral exemplarity and mentoring into everyday practice. The study concludes that charismatic leadership, when aligned with institutional values and implemented through structured mechanisms, can serve as a sustainable model for educational transformation in faith-based settings. These findings have practical implications for leadership development programs that integrate spiritual values with managerial competencies to support the holistic advancement of Islamic education in Indonesia